2010
DOI: 10.21273/hortsci.45.1.71
|View full text |Cite
|
Sign up to set email alerts
|

Nursery Worker Turnover and Language Proficiency

Abstract: The U.S. nursery and landscape industry generates 1.9 million jobs and had an annual payroll of greater than $3 billion in 2002, yet little is known about nursery and landscape workers. This lack of information is even more pressing considering that labor generally accounts for greater than 40% of production costs and 31% of gross sales. Labor shortages, immigration reform, and legal status of employees are widely reported as the industry's most critical issues. We hypothesized that relevant data regar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 12 publications
(18 reference statements)
0
12
0
Order By: Relevance
“…The nursery and greenhouse industry is often described as one of the fastest-growing sectors of U.S. agriculture and is inherently labor intensive (Regelbrugge, 2007) with greater than 40% of production costs consisting of labor costs (Mathers et al, 2010). Hodges et al (2011) estimated the total economic impact of the U.S. green industry at $175.26 billion representing %0.76% of the national gross domestic product in 2007.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The nursery and greenhouse industry is often described as one of the fastest-growing sectors of U.S. agriculture and is inherently labor intensive (Regelbrugge, 2007) with greater than 40% of production costs consisting of labor costs (Mathers et al, 2010). Hodges et al (2011) estimated the total economic impact of the U.S. green industry at $175.26 billion representing %0.76% of the national gross domestic product in 2007.…”
mentioning
confidence: 99%
“…Many commercial operations have employed immigrant labor, which is mostly less skilled, to meet their rising labor requirements. The nursery migrant workforce are employed, on average 6 months, and most stayed for 10 months (Mathers et al, 2010). In the long run, there is a need to increase the skill level of these migrant workers to improve wage rates, recruitment, and retention of workers.…”
mentioning
confidence: 99%
“…In addition to future water availability concerns, labor costs and employee management, retention, and training are persistent challenges for commercial horticulture producers. Mathers et al (2010) noted that labor accounts for 40% of nursery production costs, whereas labor retention rates were 51% after 5 years. The horticulture industry is facing critical shortfalls in labor pools with tightening regulations regarding migrant workers and an increasingly competitive domestic labor market (Bellenger et al, 2008).…”
mentioning
confidence: 99%
“…H ired farmworkers make up a third of the total agricultural labor force and are critical to U.S. agricultural production, particularly for labor-intensive sectors such as fruit and vegetable farms (Kandel, 2008). Regelbrugge (2007) described the nursery and greenhouse industry as one of the fastest-growing sectors of U.S. agriculture, and is inherently labor intensive with 40% of production costs consisting of labor costs (Kandel, 2008;Mathers et al, 2010). The most recent estimates by Hodges et al (2011) showed that the total economic impact of the U.S. green industry reached $175.26 billion representing 0.76% of the national gross domestic product in 2007.…”
mentioning
confidence: 99%
“…Many commercial operations have employed immigrant labor, which is mostly less skilled, to meet their rising labor requirements. The nursery migrant workforce are employed, on average 6 months, and most stayed for 10 months (Mathers et al, 2010).…”
mentioning
confidence: 99%